“Wegoquiz” to Improve Students’ English Achievement - Lilisuryani, Lilisuryani (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Pandemic began to enter this country around March 2020. Since then, almost all teachers, students and schools were shocked by the very sudden change. Online learning becomes one of the solution in learning.However, many students could not follow this online learning well. Therefore, the teachers have to be very careful in choosing and planning online learning media for teaching otherwise the result would be dissatisfying. This paper reports a best practice on the use of “wegoquiz”media in improving the students’ English achievement at SMAN 1 Batang Anai. It is a combination of three media in online learning. The three media are learning website with google site, google meet and quizziz. These media were used to the third year students in the first semester of 2021/2022 academic year. The result shows that by using “wegoquiz”,the students’engagement in learning process is improving a lot. They learned using the website, they attended google meet and they did the quizziz several times. As a result, their English achievement is also improving significantly.